2003
DOI: 10.1063/1.1591072
|View full text |Cite
|
Sign up to set email alerts
|

Aging characteristics of nickel contact on p-type silicon

Abstract: The effect of aging on the electrical properties of a Ni–p-Si contact was studied by measuring the electrical characteristics at different intervals of time. The current–voltage characteristics measured show a decrease in the current over time for the first few measurements at different aging times followed by an insignificant change for longer aging. The barrier height extracted from I−V characteristics was found to increase from an initial value to a final higher value after a prolonged period of aging. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…The results as shown in figure 9 indicate that the contact resistance is fairly stable with a slight fluctuation in the current in the different measurement sets, without any definite indication of ageing contrary to the reported ageing characteristics of nickel by vacuum evaporation on p-type crystalline silicon [20]. This can be attributed to the fact that during nickel deposition by vacuum evaporation, free silicon atoms are liberated by nickel bombardment due to which there is an initial increase in the barrier height whereas in nickel plating, no such nickel bombardment takes place [21].…”
Section: Ageingcontrasting
confidence: 62%
“…The results as shown in figure 9 indicate that the contact resistance is fairly stable with a slight fluctuation in the current in the different measurement sets, without any definite indication of ageing contrary to the reported ageing characteristics of nickel by vacuum evaporation on p-type crystalline silicon [20]. This can be attributed to the fact that during nickel deposition by vacuum evaporation, free silicon atoms are liberated by nickel bombardment due to which there is an initial increase in the barrier height whereas in nickel plating, no such nickel bombardment takes place [21].…”
Section: Ageingcontrasting
confidence: 62%
“…However, in this article, low‐resistance contacts on PSi have been realized by electroless nickel deposition from a very weakly alkaline solution followed by copper thickening. Kanungo et al reported that fabricated contacts were stable without significant aging which was observed for vacuum‐evaporated nickel contacts …”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 92%